2016
DOI: 10.3389/fnbeh.2015.00345
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Flavonoid-Rich Fraction on the Acquisition and Extinction of Fear Memory: Pharmacological and Molecular Approaches

Abstract: The effects of flavonoids have been correlated with their ability to modulate the glutamatergic, serotoninergic, and GABAergic neurotransmission; the major targets of these substances are N-methyl-D-aspartic acid receptor (NMDARs), serotonin type1A receptor (5-HT1ARs), and the gamma-aminobutyric acid type A receptors (GABAARs). Several studies showed that these receptors are involved in the acquisition and extinction of fear memory. This study assessed the effects of treatment prior to conditioning with a flav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 129 publications
4
17
0
Order By: Relevance
“…Our results confirm that treatment with 4 mg/kg Diazepam had an anxiolytic-like effect and impaired short-and long-term memory retention evaluated in the training and test session, respectively, in the PM-DAT task and is in accordance with data described by Silva and colleagues (Silva et al, 2016). This effect is well-established in rodents studies in different tasks (de Oliveira et al, 2014(de Oliveira et al, , 2015Silva et al, 2016) and human studies (Rich et al, 2006;Roy-Byrne et al, 1987;Verwey et al, 2005). Moreover, the increase in the total number of entries into any of the arms during testing suggest that the rats treated with Diazepam at the higher dose could not distinguish the aversive arms from the non-aversive arm in the test session in relation to rats treated with flavones (Vicenin-2 and Vitexin), which was interpreted as impaired memory retention, since no drugs were administered before the test session.…”
Section: Flavone Treatment Prior To Training Session Simultaneously Msupporting
confidence: 91%
See 1 more Smart Citation
“…Our results confirm that treatment with 4 mg/kg Diazepam had an anxiolytic-like effect and impaired short-and long-term memory retention evaluated in the training and test session, respectively, in the PM-DAT task and is in accordance with data described by Silva and colleagues (Silva et al, 2016). This effect is well-established in rodents studies in different tasks (de Oliveira et al, 2014(de Oliveira et al, , 2015Silva et al, 2016) and human studies (Rich et al, 2006;Roy-Byrne et al, 1987;Verwey et al, 2005). Moreover, the increase in the total number of entries into any of the arms during testing suggest that the rats treated with Diazepam at the higher dose could not distinguish the aversive arms from the non-aversive arm in the test session in relation to rats treated with flavones (Vicenin-2 and Vitexin), which was interpreted as impaired memory retention, since no drugs were administered before the test session.…”
Section: Flavone Treatment Prior To Training Session Simultaneously Msupporting
confidence: 91%
“…T anticonvulsant, myorelaxant and cognitive-impairing effects (de Oliveira et al, 2014(de Oliveira et al, , 2015Griffin et al, 2013;Rich et al, 2006;Verwey et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were seen after a single dose treatment with crude extract of Erythrina falcata (CE), pure flavonoids or flavonoid-rich fractions from the stem bark of E. falcata using a one-trial, step-down inhibitory avoidance (IA) [9] or conditioned lick suppression (CLS) [8] tasks.…”
Section: Introductionsupporting
confidence: 62%
“…Moreover, our data showed, through pharmacological manipulation and genetic analysis, that acquisition of lick suppression is mediated by hydroxytryptamine (serotonin) receptor, subunit 1A (5-HT 1A R), gamma-aminobutyric acid type A receptor (GABA A R) and GluN2B-NMDAR in the dorsal hippocampal formation (dHF). Furthermore, for the first time, we showed by pharmacological and molecular analysis that the fear memory acquisition is modulated by NMDAR and spontaneous recovery of fear memory, verified after treatment with flavonoidic fractions, may be reliant on tri-activation of GluN2A/GluN2B-NMDARs and 5-HT 1A R in the dHF [8]. Conversely, our findings also suggested that spontaneous recovery is not modulated by GABA A Rs.…”
Section: Flavonoidic Fraction Improves the Acquisition Of Fear Memorymentioning
confidence: 37%
See 1 more Smart Citation